Melatonin as an Antioxidant and Immunomodulator in Atopic Dermatitis-A New Look on an Old Story: A Review - Andrzej Kazimierz Jaworek; Jacek Cezary Szepietowski; Przemysław Hałubiec; Anna Wojas-Pelc; Jolanta Jaworek (MDPI AG, 2021)
Atopic dermatitis (AD) is common inflammatory dermatosis, typically with chronic and recurrent course, which significantly reduces the quality of life. Sleep disturbances are considered to be remarkably burdensome ailments in patients with AD, and are routinely included during assessment of disease severity. Therefore, endogenous substances engaged in the control of circadian rhythms might be important in pathogenesis of AD and, possibly, be used as biomarkers of disease severity or even in development of novel therapies. Melatonin (MT), the indoleamine produced by pineal gland (but also by multiple other tissues, including skin), plays a pivotal role in maintaining the sleep/wake homeostasis. Additionally, it possesses strong antioxidant and anti-inflammatory properties, which might directly link chronic skin inflammation and sleep abnormalities characteristic of AD. The objective of this work is to systematically present and summarize the results of studies (both experimental and clinical) that investigated the role of MT in the AD, with a focus on the antioxidant and immunomodulatory effects of MT.